Bird of the Farallons - Luger, Harriett 1914-2012; Hampshire, Michael A. ([Reading, Massachusetts] Young Scott Books, 1971)
Describes the life of a California murre and his experiences with a human family after he swims into an oil slick.
Keywords: Murres -- Juvenile literature; Birds -- California -- Juvenile literature; Murres; Birds -- California